(IN)EXCLUSION OF PEOPLE WITH INTELLECTUAL DISABILITIES UNDER THE PRISM OF THE DIGNITY OF THE HUMAN PERSON (CIPEEX, 2025)
Intellectual disability is a condition characterized by below-average cognitive abilities, together with impairments in social and mental functioning. This study sets out to explore the social exclusion faced by individuals with intellectual disabilities, from the perspective of the dignity of the human person. The main objective is to investigate the social exclusion faced by individuals with intellectual disabilities, analyzing this situation from the perspective of the dignity of the human person. To achieve this goal, three specific objectives were established: a) To historically and conceptually contextualize people with disabilities; b) To address the legal provisions that deal with people with disabilities; c) To analyze the social inclusion or exclusion of these people from the perspective of human dignity. The study used bibliographical research to review academic literature on intellectual disability and social inclusion; and documentary research to analyze legislation, public policies and official documents related to the protection and inclusion of people with disabilities. The results showed that the inclusion of people with intellectual disabilities is not just limited to their inclusion in educational environments. Inclusion must encompass the entire physical and social environment in order to guarantee the full participation of these individuals in society. It was observed that, despite legal and political advances, there are still significant barriers that prevent the true inclusion of these people. The research revealed that the dignity of the human person is not being fully respected in many contexts, due to prejudice and a lack of adequate infrastructure. The effective inclusion of people with intellectual disabilities requires a holistic approach that goes beyond education. It is essential that the physical and social environments are adapted to facilitate the full participation of these people in society. Existing public policies and legislation need to be implemented in a more effective and practical way to guarantee the dignity and rights of these individuals. For inclusion to be effective, it is essential that the necessary adaptations are integrated into everyday practice, promoting a more inclusive and respectful society. This study highlights the importance of an ongoing commitment to adapting environments and implementing inclusive policies, ensuring that the dignity of the human person is always a priority in the inclusion of individuals with intellectual disabilities.
Keywords: human rights; social exclusion; individuals with disabilities